Studi Hubungan Ruralisasi Dengan Penduduk Lokal: Pola Kerukunan Hidup Umat Beragama Di Daerah Pinggiran Jakarta - Muhammad Ridwan Lubis; Bambang Irawan; Amirsyah Tambunan (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
There are four types patterns of shifting population due to the influence of modernity, namely ruralization, urbanization, transmigration and circulation. Ruralization is the movement from city to village while urbanization is moving from village to city. Migration is a permanent migration of people from one area to another. Finally, circulation is the movement of people to fulfill certain interests such as work and living in two different places, so they must move every day from village to city. This research focuses on the Study of the Relationship between Ruralization and Local Residents: The Pattern of Religious Harmony in the Suburbs of Jakarta. The overflow of Jakarta's population is accommodated by new growth areas which are then concluded to be Jakarta, Bogor, Depok, Tangerang, Bekasi. The occurrence of this displacement is due to a push factor from the area of origin, a pull factor from the destination. Attractor factor is the hope of getting opportunity to improve their standard of living and religious, political, and ethnic considerations in the area of origin. Eventhough religion is another factor but residents of villages as rural targets have religious affinity that is inherent in religious identity with ethnic groups, especially Betawi ethnic groups as local residents with migrants residents. Religious factors as a basis for determining the work ethic of social cohesiveness in this case religious harmony. Therefore, a strategy is needed to build social cohesiveness due to culture and diversity to avoid social tensions.